Efektifitas Media Infografis Dalam Peningkatan Pengetahuan Pemberian Makanan Bayi Dan Anak - Andini Surijati, Katri; Darmawati, Dwita; Widanita, Neva; Rahmawati, Regina; Lastariadi, Yurisadensi Eka Putri; Permadi, M Rizal (Politeknik Negeri Jember, 2024)
Improving nutrition and improving the health status of infants can be done through growth monitoring and nutritional status assessment at posyandu every month. During posyandu activities, a nutrition intervention or counselling through infographic also carried out to increase maternal awareness of good infant feeding. The aim of the study was to determine the increase in knowledge and infant feeding by mothers in Sumbang Village after the nutritional intervention. This study design used experimental method with counselling using infographic media to 48 mothers of infants and toddlers. The bivariate analysis used was Wilcoxon test. A p value of 0.03 was obtained for changes in knowledge level and a p value of 0.04 for changes in feeding practices both before and after the intervention. The use of infographic media was effective enough in improving knowledge and feeding practices of infants and toddlers in Sumbang Village, Sumbang District.